Value Creation Acceptance, Price Tolerance, and Local Wisdom-Based Conservation Knowledge as Determinants of Repurchase Intention: A Study on the Coffee Industry in Indonesia - Carolina, Deasy (Journal Research of Social Science, Economics, and Management, 2025)
The background of this research originates from the phenomenon of Indonesian coffee market dynamics, characterized by increasing price instability and performance fluctuations due to climate change and sustainability challenges. In this context, the level of consumer tolerance for brand performance is one of the important factors in maintaining consumer loyalty and market stability. This study aims to analyze the relationship between the co-creation process, tolerance to brand performance, and conservation knowledge based on local wisdom as a moderating variable. This study uses an explanatory quantitative approach, with a population of 3,178 social media followers from local coffee brands that apply conservation principles based on local wisdom. The number of respondents successfully collected was 358, with the characteristics of a majority of men (193 respondents), aged 29–43 years (millennial generation), and from Central Java (190 respondents). Data were collected through an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the relationships between variables. The results of the analysis show that the acceptance of value creation has a positive effect on price tolerance. Furthermore, conservation knowledge based on local wisdom has been shown to positively moderate the relationship between performance tolerance and repurchase intention. This research makes an important contribution to the development of the theory of equal value creation in the context of sustainable marketing, especially by integrating the conservation aspect of local wisdom as a cultural factor that can strengthen the relationship between consumers and brands.